ChemInform Abstract: UV Light‐Mediated Difunctionalization of Alkenes with CF3SO2Na: Synthesis of Trifluoromethyl Phenanthrene and Anthrone Derivatives. Issue 42 (September 2016) - Li, Bing; Fan, Dan; Yang, Chao; Xia, Wujiong
Abstract: The benzophenone‐catalyzed photoreaction of α, β‐unsaturated ketones affords trifluoromethyl‐containing phenanthrenes, whilst the analogous anthraquinone‐catalyzed reaction of γ, δ‐unsaturated ketones gives rise to trifluoromethylated anthrone derivatives.